2018
DOI: 10.1103/physrevmaterials.2.054407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in situ electric-field-assisted growth on antiphase boundaries in epitaxial Fe3O4 thin films on MgO

Abstract: Anti-phase boundaries (APBs) normally form as a consequence of the initial growth conditions in all spinel ferrite thin films. The presence of APBs in epitaxial films of the inverse spinel Fe 3 O 4 alters their electronic and magnetic properties due to strong antiferromagnetic (AF) interactions across these boundaries. The effect of using in-situ electric field assisted growth on the migration of APBs in hetero epitaxial Fe 3 O 4 (100)/MgO(100) thin films have been explored in the present work. The electric fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
5
7
0
Order By: Relevance
“…Secondly, it has been reported that the magnetization is not saturated under the effect of high magnetic fields of 70 kOe [8], which means that exchange interactions are most likely to be responsible of this behavior. Furthermore, a recent work suggested that the strength of APB exchange interactions is reduced by applying electric fields during the synthesis process, as a consequence showing saturation fields of µ 0 H = 150 mT [12] which is similar to bulk results. Finally, it has been demonstrated that when the samples are grown with low density of APBs, the number of magnetic domains observed is smaller than in samples with lots of APBs, pointing to them as a source of magnetic domains [11].…”
Section: Introductionsupporting
confidence: 81%
“…Secondly, it has been reported that the magnetization is not saturated under the effect of high magnetic fields of 70 kOe [8], which means that exchange interactions are most likely to be responsible of this behavior. Furthermore, a recent work suggested that the strength of APB exchange interactions is reduced by applying electric fields during the synthesis process, as a consequence showing saturation fields of µ 0 H = 150 mT [12] which is similar to bulk results. Finally, it has been demonstrated that when the samples are grown with low density of APBs, the number of magnetic domains observed is smaller than in samples with lots of APBs, pointing to them as a source of magnetic domains [11].…”
Section: Introductionsupporting
confidence: 81%
“…Secondly, it has been reported that the magnetization is not saturated under the effect of high magnetic fields of 70 kOe [5], which means that exchange interactions are most likely to be responsible of this behaviour. Additionally, a recent work suggested that the strength of APB exchange interactions is reduced by applying electric fields during the synthesis process, as a consequence showing saturation fields of µ 0 H = 150 mT [9] which is similar to bulk results. Finally, it has been demonstrated that when the samples are grown with low density of APBs, the number of magnetic domains observed is smaller than in samples with lots of APBs, pointing to them as a source of magnetic domains [8].…”
Section: Introductionsupporting
confidence: 81%
“…Thus, APBs have been suggested to be responsible of the different magnetic properties observed in samples made of the same material, with the same nanostructure, but created with different techniques, e.g, the saturation magnetization in magnetite nanoparticles [4] or the magnetic anisotropy in magnetite thin films [5][6][7]. In fact, recent works on magnetite thin films have given confidence on this supposition, showing that when the nanostructure is grown achieving a low density of APBs [7,8] or reducing their strength by applying an electric field during the synthesis [9], the magnetic properties not only begin to match between all the samples, but they start to be similar to the bulk case.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been proposed that the existence of APBs contributes to fatigue-free ferroelectricity . From a magnetic point of view, the unusual magnetoresistance in Fe 3 O 4 has been shown to be strongly dependent on the density of APBs. , …”
Section: Introductionmentioning
confidence: 99%
“…22 From a magnetic point of view, the unusual magnetoresistance in Fe 3 O 4 has been shown to be strongly dependent on the density of APBs. 23,24 Due to their attractive possibility to modify and enhance functional properties, research into APBs has been extensive. This includes understanding the fine structure, such as atomic arrangements, 25 habit planes, 26 translational vectors, 27 and the associated effects on defect chemistry and charge accumulation.…”
Section: ■ Introductionmentioning
confidence: 99%